2016
DOI: 10.1007/s10518-016-9920-9
|View full text |Cite
|
Sign up to set email alerts
|

Seismic response of Beirut (Lebanon) buildings: instrumental results from ambient vibrations

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 50 publications
3
22
0
Order By: Relevance
“…Pre-1974 high-rise buildings were constructed with C N 15 and low-rise buildings with C N 24. In such a case, (1) this is inconsistent with the single C N value found by Oliveira (2004), Michel, Guéguen, Lestuzzi, et al (2010), and Salameh et al (2014) for both types of buildings, (2) the difference cannot be explained, as at the time there was no building code, and thus the constructive system was identical for both types of buildings. Moreover, it would imply that the buildings have not been affected, neither by aging nor by earthquakes, including the 1974 event, and thus they would still be able to sustain a 30%-35% loss of frequency before entering into a hazardous frequency domain (Dunand et al, 2004(Dunand et al, , 2006.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Pre-1974 high-rise buildings were constructed with C N 15 and low-rise buildings with C N 24. In such a case, (1) this is inconsistent with the single C N value found by Oliveira (2004), Michel, Guéguen, Lestuzzi, et al (2010), and Salameh et al (2014) for both types of buildings, (2) the difference cannot be explained, as at the time there was no building code, and thus the constructive system was identical for both types of buildings. Moreover, it would imply that the buildings have not been affected, neither by aging nor by earthquakes, including the 1974 event, and thus they would still be able to sustain a 30%-35% loss of frequency before entering into a hazardous frequency domain (Dunand et al, 2004(Dunand et al, , 2006.…”
Section: Discussionmentioning
confidence: 71%
“…; in France (C N ≈ 25) by Michel,Guéguen, Lestuzzi, et al (2010); and in Lebanon (C N ≈ 25) bySalameh et al (2014).…”
mentioning
confidence: 96%
“…Most seismic codes assume a 5% constant value of damping without correlating it with the fundamental period of the structure. In a recent study, Salameh et al [58] demonstrated that the damping is related to the soil foundation and the building geometry. In our study it appears also evident a variability linked to the different rigidity of this complex structure as a function of the longitudinal or transversal orientation of its structural elements.…”
Section: Ambient Vibration Measurementsmentioning
confidence: 99%
“…Regarding site information, a total of 827 sites were measured for the Beirut City area (Brax 2013;Salloum et al 2014;Salameh et al 2016) to obtain the soil resonance frequency map of Beirut using HVSR (horizontal to vertical spectral ratio) approach (Nakamura 1989). The large density of measurements allowed to derive interpolated maps of both soil frequency and A 0HV amplitude, which could in turn be used to estimate the f struct /f soil and A 0HV values for each of the 7692 buildings.…”
Section: Application To Beirutmentioning
confidence: 99%